How Schools Meet Students' Needs : Inequality, School Reform, and Caring Labor - Kerstetter, Katie (Book collections on Project MUSE., 2023)
"Meeting students' basic needs - including ensuring they have access to nutritious meals and a sense of belonging and connection to school - can positively influence students' academic performance. Recognizing this connection, schools provide resources in the form of school meals programs, school nurses, and school guidance counselors. However, these resources are not always available to students and are not always prioritized in school reform policies, which tend to focus more narrowly on academic learning. This book is about the balancing act that schools and their teachers undertake to respond to the social, emotional, and material needs of their students in the context of standardized testing and accountability policies. Drawing on conversations with teachers and classroom observations in two elementary schools, How Schools Meet Students' Needs explores the factors that both enable and constrain teachers in their efforts to meet students' needs and the consequences of how schools organize this work on teachers' labor and students' learning"--